An Analysis of the Processes Shaping the Value Chain in Enterprise - Walas-Trębacz, Jolanta (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Today's enterprises are forced to identify and change the whole chain of value creation for the customer, which usually extends beyond its borders. An important stage in the analysis of an enterprise's value chain is identifying the processes carried out in the organisation and evaluating how effectively and efficiently they are achieved, which is possible by establishing and developing specific measures and methods of measuring these processes. The purpose of this article is to provide a method for increasing the value of the enterprise, based on the analysis of processes involved in the enterprise's value chain. The paper explains the basic concepts of process, system processes and process management, defines the value chain and shows the structure of the processes that shape it. The main part of the article presents the methodology of the analysis process, which consists of the following stages: identifying the processes carried out in the enterprise, indicating the role of the processes in creating added value for the customer, measurement and evaluation of the results of processes, and determining process improvement proposals.